Journal of ICT - Universiti Utara Malaysia (Universiti Utara Malaysia Press, 2002)
"This journal covers all aspects of information and communication technology, its theories and applications."
Keywords: Information technology : Periodicals; Communication : Periodicals; Communication; Information technology